Ziarah Sebagai Instrumen Silaturahmi: Analisis Semantik Hadis Perspektif Toshihiko Izutsu - Rizky Sulaiman; Hawwin Huda Yana; Nurdiana Sari; Dedi Andrianto (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes the conceptual relationship between ziarah (visiting) and silaturahmi (maintaining kinship ties) from the perspective of hadith and reconstructs the meaning of ziarah which has undergone semantic reduction among contemporary Indonesian Muslim society. Using a qualitative approach with library research method, this study applies Toshihiko Izutsu's semantic analysis, distinguishing between basic meaning and relational meaning. Primary data sources include major hadith collections such as Shahīh al-Bukhārī, Shahīh Muslim, and Sunan al-Tirmidzī. The findings reveal that the relationship between ziarah and silaturahmi is instrumental-normative: ziarah serves as an instrument of social action to actualize silaturahmi as a moral value. The basic meaning of ziarah is "to visit" in a general sense, but it has narrowed to mean solely "grave visitation." The reconstruction restores ziarah to its three dimensions: vertical-spiritual, horizontal-social, and cultural-educative. In conclusion, ziarah is not limited to graves but includes social visits to fellow living beings as an implementation of silaturahmi